Characterisation and selection of freshwater cyanobacteria for phycobiliprotein contents - Hui, Teng Tan; Md. Yusoff, Fatimah; Yam, Sim Khaw; Nazarudin, Muhammad Farhan; Noor Mazli, Nur Amirah Izyan; Ahmad, Siti Aqlima; Shaharuddin, Noor Azmi; Toda, Tatsuki (Springer Nature, 2022)
Some cyanobacteria species have a high capacity for accumulating phycobiliprotein contents in their cells. However, there is a lack of information on screening tropical freshwater cyanobacteria, particularly phycobiliproteins. In addition, it is unclear which characteristics of cyanobacteria (morphological and/or growth) could affect phycobiliprotein contents. This study aimed to screen and characterise Malaysian indigenous freshwater cyanobacteria for the growth, biomass, and pigment contents and determine the major characteristic that contributed to the variation of phycobiliproteins. The surface/volume (S/V) ratio, specific growth rate, biomass productivity, and pigment contents of the isolated cyanobacteria were analysed. Principal component analysis (PCA) and hierarchical cluster analysis (HCA) were applied to distinguish the factor responsible for phycobiliprotein variations in cyanobacteria. For the phycobiliprotein contents, Arthrospira sp., Pseudanabaena sp., and Synechococcus elongatus showed significantly higher (p < 0.05) amounts of cyanobacterial phycocyanin (C-PC), phycoerythrin (C-PE), and allophycocyanin (C-APC), respectively, than other studied cyanobacteria. This study showed no apparent trend of similarity and difference between the unicellular and filamentous cyanobacteria. In addition, carotenoid contents demonstrated a positive correlation with total phycobiliproteins, C-PC and C-APC. Based on the current findings, Arthrospira sp., Pseudanabaena sp. and Synechococcus elongatus might be the promising candidate to be the C-PC, C-PE and C-APC sources, respectively, for commercial production purposes. The selection of optimal cyanobacterial strain is crucial for efficient phycobiliprotein production. This study underlined the potential of freshwater cyanobacteria in producing respective and total phycobiliproteins. Future studies such as the optimization process should be adopted to improve the phycobiliprotein production of these cyanobacteria significantly.